PERBANDINGAN AKUNTANSI KONVENSIONAL DAN AKUNTANSI SYARIAH MENURUT PEMIKIRAN SOFYAN SYAFRI HARAHAP - Ahmad Riyansyah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
The purpose of this study is to analyze the comparison of conventional accounting and Islamic accounting derived from the thoughts of Sofyan Syafri Harahap. Currently, the implementation of Islamic accounting is not widely practiced even neglected by companies due to the lack of introduction and concentration of Islamic accounting knowledge. This is because there are still few researchers who study and formulate the practice of Islamic accounting. The form of this research is qualitative through a descriptive approach. The method of the data collection is carried out through various sources including literature review of several related books, articles and related dissertations. Based on the analysis results, it is found that in comparison Sofyan Syafri Harahap argues that conventional accounting has many drawbacks. This is evident from the content of the verses in the Al-Qur'an and also the opinion of several previous Islamic scholars such as Lucas Pacioli. Islamic accounting must be able to guarantee that the information compiled or presented must be correct and free from elements of fraud or injustice, free from partiality to certain interests. The information provided must be transparent, tested, and can be accounted for in the afterlife. Knowledge of Islam is absolutely necessary to view accounting from an Islamic perspective.